2020
DOI: 10.21203/rs.3.rs-74176/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-sectional study of the prevalence, density and risk factors associated with malaria transmission in urban communities of Ibadan, Southwestern Nigeria

Abstract: Background Malaria is a serious global public health challenge which causes great morbidity and mortality worldwide particularly in sub-Saharan Africa. This study was designed to determine the prevalence, parasite density and risk factors associated with malaria infection transmission among residents of two urban communities of Ibadan, southwestern Nigeria. Methods A cross-sectional hospital-based study was carried out on 300 participants. Blood samples were obtained. Thick and thin blood films were prepared… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 26 publications
(30 reference statements)
2
18
6
Order By: Relevance
“…Prevalence was highest among those with secondary education and least among those without formal education. This is in contrast with the findings of Awosolu et al, [39] who recorded a higher prevalence among those with formal education. Amongst the different types of occupation, artisans had the highest prevalence whereas the unemployed had the least prevalence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Prevalence was highest among those with secondary education and least among those without formal education. This is in contrast with the findings of Awosolu et al, [39] who recorded a higher prevalence among those with formal education. Amongst the different types of occupation, artisans had the highest prevalence whereas the unemployed had the least prevalence.…”
Section: Discussioncontrasting
confidence: 99%
“…Amongst the different types of occupation, artisans had the highest prevalence whereas the unemployed had the least prevalence. This is in line with the findings of Awosolu et al, [39] but in contrast with findings of Kalu et al, [36] who recorded a higher prevalence amongst farmers. This difference could be attributed to higher stress levels induced by the nature of their job.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies by Awosolu et al [18] showed a cross-section of malaria transmission prevalence in Ibadan. The study indicated that malaria infection was observed to be caused by P. falciparum and out of 300 selected individuals observed, 56.4% of malaria infection was categorized as low (< 1000 parasite/µL of blood), and 43.6% were classified as moderate with a range of 1000≤9999 parasite /µL of blood.…”
Section: Prevalence Of Malaria In Nigeriamentioning
confidence: 99%
“…The parasites were maintained by serial passage of blood collected from an infected donor animal to an uninfected mouse using the method of Aina et al [11]. Each mouse was inoculated with 1x10 6 parasitized red blood cells suspension blood in phosphate buffer saline. The newly infected animals were left for 7days for the parasite to manifest.…”
Section: Malaria Parasite (Plasmodium Berghei)mentioning
confidence: 99%
“…Globally, it is estimated that 3.2 billion people are at risk of contracting malaria annually [5]. In Nigeria, malaria is transmitted throughout the year, with more than 194 million people predisposed to contracting malaria infection [6]. There is a vaccine currently available for malaria as of 2021.…”
Section: Introductionmentioning
confidence: 99%